Coding as Sport. - Kirkpatrick, Keith (Communications of the ACM, 2016)
The article explains how programming competitions help and reward those who excel in sport coding. Topics discussed are the opportunity for participants to benchmark their progress and showcase their skills to prospective employers at coding contests, gender gap in coding competitions, and the importance of collaborative approach, efficiency and time management to completing a coding project.